2016
DOI: 10.1016/j.ijid.2016.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of replacement of circulating viruses by seasonal and pandemic influenza A viruses

Abstract: The findings of this study on replacement mechanisms could lead to a better understanding of virus transmission dynamics and may possibly be helpful in establishing an effective strategy to mitigate the impact of seasonal and pandemic influenza.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…We believe these factors may have protected children from infections due to seasonal viruses. It has also been reported that the pandemic virus can replace normal seasonal viruses due to its high initial susceptibility and basic reproduction number [ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…We believe these factors may have protected children from infections due to seasonal viruses. It has also been reported that the pandemic virus can replace normal seasonal viruses due to its high initial susceptibility and basic reproduction number [ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…The consequences of antigenic variation can include persistent viral infection 4 , pandemics of diseases 5 , and reinfection after recovery 6,7 . Antigenic variation can also impact therapeutics or vaccine efficacy, as it confounds development of treatments and vaccines that can protect against diverse viral strains 7-9 .…”
Section: Introductionmentioning
confidence: 99%
“…Initiation of seasonal influenza epidemics is mostly associated with rate of influenza virus change, strain replacement, availability of susceptible hosts and climatic conditions [ 44, 45 ]. Further study of virus interference is warranted and could inform our understanding of human respiratory diseases that exhibit temporal trends such as exacerbations of asthma and chronic obstructive pulmonary disease, otitis media and allergic rhinitis.…”
Section: Discussionmentioning
confidence: 99%